An Analysis of Spatial Relations in Croatian: A Cognitive Approach - Žic Fuchs, Milena (Array, 1994)
In Croatian, as in other similar languages, spatial relations are predominantly expressed by prepositions and other deictic expressions. Until now, no systematic attempt has been made to analyze language acquisition in Croatian, and this is especially felt in specific domains such as spatial relations, which are interesting not only linguistically but also cognitively. The preliminary analysis of a pilot study of metalinguistic knowledge and spatial relations showed that the subjects had difficulties in dealing with spatial prepositions in sentence production in Croatian. This triggered off furtehr investigation on a broader range of subjects (starting from pre-school to college students) that tested both their linguistic and conceptual competence in dealing with spatial relations. We discuss the implications of these findings in terms of the relationship between linguistic and cognitive determinants expressing spatial relations.